Comparison of safety and effectiveness between phacoemulsification and suture less small incision procedures in Cataract surgery - Asma Aftab; Imran Khan; Yaseen Lodhi; Marrium Shafi; Saad Rauf Khan (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Cataract is major cause of preventable blindness, worldwide. Phacoemulsification and manual small incision are most common surgical methods of cataract. The objective of our study was to compare surgical outcomes and complications in phacoemulsification (Phaco) and manual small incision cataract surgery (MSICS) patients